Island biogeography of terrestrial snail from islands of Sabah, Malaysia - Phung, Chee Chean (2018)
Islands always held special attraction to scientist as model systems in biogeography and evolutionary studies. In Sabah, there are about 500 islands with various degree of isolation and size, and have experienced different climatic or historical processes. These attributes promise high research potential particularly in the field of island biogeography. Unfortunately, the up-to-date knowledge about the island biodiversity in Sabah is scarce in spite of the fact that Sabah is situated within one of the megabiodiversity hotspots. In addition, the geographical, ecological and evolutionary factors that shaped the Sabah’s islands biodiversity pattern are yet to be tackled. Using land snail as subject, an annotated checklist of land snail from 24 west coast islands of Sabah was presented and was explained the effect of island area, isolation on species composition and species richness. The phylogeography pattern of selected land snail species (i.e. Leptopoma pellucidum) from northwest islands was also demonstrated to understand the present genetic distribution and structure, and infer underlying historical processes by calibrating the phylogenetic tree with molecular clock. A total of 67 land snail species were documented from 24 west coast islands of Sabah based on 133 systematic sampling plots, collection database and published records. Land snail composition pattern was influenced by both isolation and area. The results of this study demonstrated that the species richness on Sabah’s island was largely determined by interaction among island area and isolationWith respect to phylogeography of L. pellucidum from northwest islands, the results revealed that its genetic structure was categorised into three major lineages. Suprisingly, time-calibrated tree showed that the genetic divergence time does not correspond with island isolation due to sea level rising during Last Glacial Maximum. The lineages were estimated to have diverged during the middle and late Pleistocene. Earlier periodic interglacials and Pleistocene climate fluctuation might caused intra-specific divergence. This study reveals biogeography and evolutionary processes of Borneo’s island. This study also contribute to island biodiversity management plan as island size can be the relevant variable in conserving land snail diversity.